Overcontrol, Prevention and Treatment of Hypertension Through Health Counseling in North Margahayu Village, Bandung City - Ardayani, Tri; Damayanti Saragih, Berlyna; Melia, Stephanie; Rejeki, Sri; Sinaga, Herwinda; Adie, Yohanes; Tanti, Lanny (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2023)
Hypertension can be defined as a condition where a person's blood pressure becomes too high or commonly known as high blood pressure. Hypertension has become a global health problem, including in Indonesia, uncontrolled blood pressure can cause complications in body organs such as the kidneys, heart, brain, retina of the eye, and blood vessels, hypertension becomes dangerous because it rarely shows symptoms, so most people with hypertension are not aware of it. if he has uncontrolled blood pressure. Implementation Methods, Health counseling methods used in community service activities at RW 09 Babakan Ciparay Bandung City Lectures and questions and answers using power point media, counseling was carried out on September 13, 2022 at the RW 09 office attended by 35 people. The level of public understanding about the prevention and treatment of hypertension increases, people can maintain their diet, manage stress and activities and carry out routine checks on health services. In conclusion, community service activities in the form of health counseling on the prevention and treatment of hypertension went smoothly, and were attended by 80% of the people of RW 09 Babakan Ciparay, Bandung City. Suggestions that can be conveyed to the community RW 09 Babakan Ciparay can apply all the knowledge that has been conveyed in community service activities carried out by the Immanuel Health Institute and suggestions for the Immanuel Health Institute that this activity should be carried out regularly every semester so that public knowledge about health increases.